Comparative economic analysis of stake, hanging, and raft methods of mussel farming in the Province of Capiz - Dionio, Marie Vivien Alzona (1988.)
The importance of mussels as a primary crop has been recognized. Its potentials as a protein-rich source of food has resulted in the growth of interest in mussel culture. There are presently several culture methods used in mussel farming and studies are needed to determine which culture method is the most productive and most profitable for the country's mussel industry. In this connection the study examines the profitability of the different methods of mussel farming. It compares the profitability of the stake, hanging, and raft culture methods with the use of the cost and return analysis. It also uses the production function analysis to determine the significant determinants of mussel production.
Thesis (Undergraduate, Bachelor of Arts in Economics) College of Arts and Sciences,University of the Philippines in the Visayas, Miagao, Iloilo.
Keywords: Mussel Farming -- Capiz